2008
DOI: 10.1021/np800303t
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Polyketides from a Marine-derived Fungus Aspergillus glaucus

Abstract: Eight new aromatic polyketides (2, 4-6, 8, 14, 16, and 17) together with eight known analogues (3, 7, 9-13, and 15) were isolated from the marine-derived fungus Aspergillus glaucus. The structures and stereochemistry of the new compounds were elucidated by spectroscopic and chemical methods, and their cytotoxicities were evaluated against the HL-60 and A-549 cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 30 publications
2
93
0
Order By: Relevance
“…The relative structure of dianthrone derivatives was unable to be confirmed by NOESY experiments (Lenta et al 2008; Haasnoot et al 1980; Spassov 1971). Indeed, the ROESY spectrum correlations of H-10 with H-4, H-5, H-4′ and H-5′, and H-10′ with H-4, H-5, H-4′ and H-5′ indicated that the relative structure of 1 cannot be confirmed by NOESY.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative structure of dianthrone derivatives was unable to be confirmed by NOESY experiments (Lenta et al 2008; Haasnoot et al 1980; Spassov 1971). Indeed, the ROESY spectrum correlations of H-10 with H-4, H-5, H-4′ and H-5′, and H-10′ with H-4, H-5, H-4′ and H-5′ indicated that the relative structure of 1 cannot be confirmed by NOESY.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the 1D NMR spectrum of 1 with those of physcion dianthrones, emodin dianthrones, and physcion-emodin dianthrones (Donald et al 1976; Du et al 2008; Monache et al 1991) suggested 1 could be a C-10/C-10′ isomer of physcion-emodin dianthrone glycosides. The 13 C NMR and DEPT spectra (Table 2) exhibited 37 carbon signals, including 31 carbon signals of physcion-emodin dianthrones that were categorized by DEPT and HSQC techniques into 18 quaternary carbons, including with two carbonyl groups [ δ C 191.3 (C-9′) and 188.5 (C-9)], 10 methine groups [ δ C 117.3 (C-2), 121.8 (C-4), 112.5 (C-5), 107.7 (C-7), 117.7 (C-2′), 122.2 (C-4′), 109.7 (C-5′), 100.7 (C-7′), 57.7 (C-10) and 56.7 (C-10′)], two methyl groups [ δ C 21.8 ( Me -3) and 22.1 ( Me -3′)], one methoxy group δ C 56.5 (O Me -6′)] and six carbon signals characteristic of glucose [ δ C 106.1, 74.9, 78.8, 71.2, 77.4, 62.7].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] They are also regarded as important intermediates in the biosyntheses of photosensory pigments with ingestion-deterrent, antiviral, and sedative properties, and some have been obtained as intermediates in the chemical syntheses of these pigments. 11,12 Additionally, the photochromic derivatives with a double bond between C-10 and C-10 0 have attracted much attention for molecular electronics, and they may be taken as potential structural elements in supramolecular assemblages due to the conductance-switching property.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed inspection of the NMR data (Table 1) of 2 with those of 1 revealed that these two compounds were very similar, except for the sugar moiety. The sugar residue in 2 was defined as a ribose by comparing the NMR data (Table 1) with those of naphthyl ribofuranoside, isotorachrysone-6- O -α- d -ribofuranoside [20], chromene glycoside, and sterin A [21]. The key HMBC correlation from H-1″ to C-3′ (Figure 2) established the connection between the ribose and diphenyl ether moiety.…”
Section: Resultsmentioning
confidence: 99%